2016
DOI: 10.1155/2016/8914769
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Selecting Optimal Number of Sensors to Improve the Credibility

Abstract: With the development of sensors, it is possible to embed many sensors within a certain space, which makes the monitor and alarm system with multisensor possible. There are two important parameters in a monitor and alarm system, namely, the false alarm rate and the missed alarm rate. In this work, a method for selecting optimal number of sensors in the sensor array is presented to improve the credibility. The influence factors of the weights and the false alarm rate and the missed alarm rate of one sensor and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Four major types of automated calibration approaches have been developed and tested till date: a) Uni-Gas Uni-Sensor Calibration; b) Uni-Gas Multi-sensor ENB Calibration; c) IoT-based Networked Multi-Gas ENB Calibration; and d) Climate Smart Heterogeneous ENB Calibration. The recent work realized a plethora of efforts made in gas sensors calibration [114][115][116][117][118][119][120][121][122][123][124][125][126][127] presented in Figures 23-26.…”
Section: Indoor Epidemiology-based Calibration and Testing Of Aq Gas ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Four major types of automated calibration approaches have been developed and tested till date: a) Uni-Gas Uni-Sensor Calibration; b) Uni-Gas Multi-sensor ENB Calibration; c) IoT-based Networked Multi-Gas ENB Calibration; and d) Climate Smart Heterogeneous ENB Calibration. The recent work realized a plethora of efforts made in gas sensors calibration [114][115][116][117][118][119][120][121][122][123][124][125][126][127] presented in Figures 23-26.…”
Section: Indoor Epidemiology-based Calibration and Testing Of Aq Gas ...mentioning
confidence: 99%
“…In 2009, the first structured gas sensors calibration system was designed and implemented by a measurement calibration system that was developed by Casey, J.G. et al [114] presented in the Figure 23 (a). A standard AQS Calibration follows the [114] schematic as: a) An Air-sealed chamber with inflow and outflow valves; b) mass flow controllers (MFCs) for the desired concentration of gas from a cylinder or a PID controller gas flow loop; c) gas cylinders with different concentrations; d) temperature actuator (heater); e) humidity actuator (steam regulator); f) gas collectors for the environmental model; g) measurement instruments other than gas sensors for comparison interfaced with a computer.…”
Section: Uni-gas Uni-sensor Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, the first structured gas sensors calibration system was designed and implemented by a measurement calibration system that was developed by Octavian et al [114]. A standard AQS Calibration follows the [114] schematic as: a) An Air-sealed chamber with inflow and outflow valves; b) mass flow controllers (MFCs) for the desired concentration of gas from a cylinder or a PID controller gas flow loop; c) gas cylinders with different concentrations; d) temperature actuator (heater); e) humidity actuator (steam regulator); f) gas collectors for the environmental model; g) measurement instruments other than gas sensors for comparison interfaced with a computer. The recent work realized a plethora of efforts made in gas sensors calibration [114][115][116][117][118][119][120][121][122][123][124][125][126][127] presented in Figures 23-26 In Figure 23a, an industry-standard instrumentation topology, i.e.…”
Section: Low-cost Calibration and Testing Of Aq Gas Sensorsmentioning
confidence: 99%
“…The previous works have showed that temperature modulation of sensors can improve selectivity [17][18][19], while more complicated algorithms are required [20]. In the last ten years, the focus has been on analysis of dynamic sensor signals [21][22][23][24], and the Fast Fourier Transform (FFT) or the Discrete Wavelet Transform (DWT) [25,26] for feature extraction has been frequently used. Many scholars used the FFT transform to extract the harmonic components as the features (e.g., Vergara and coworkers computed the absolute values of FFT and extracted the values of six harmonics corresponding to six modulating frequencies) [27].…”
Section: Introductionmentioning
confidence: 99%